Does cash crop adoption detract from childcare provision? evidence from rural Nepal - Paolisso, Michael J.; Hallman, Kelly; Haddad, Lawrence J.; Regmi, Shibesh (International Food Policy Research Institute, 2001)
Using data from fieldwork conducted in Nepal, the impact of a project designed to commercialize vegetables and fruits — the Vegetable and Fruit Cash Crop Program (VFC)— on male and female time allocation is examined. Using a rigorous time collection methodology, activity patterns in households that adopt and do not adopt the new technology are profiled. Very few studies examine changing activity patterns of both men and women in response to commercialization of agriculture. Though women’s time is valuable in agriculture, it is also valuable in the production of child nutrition. The recent evolution in thinking as to the causes of child malnutrition—the three pillars being food intake, health, and time to care—warrants further analyses of the time trade-offs that women and men face when adopting new agricultural technologies. The VFC program was successful at targeting both men and women farmers in the sense that household participation resulted in increased head male and head female time spent growing vegetables and fruits. The responses varied, however, by the number of preschool children in residence. In households with more than one preschooler, the time trade-offs associated with VFC participation were not sizeable for the care of children under 5 years. In households with just one preschooler, the trade-offs were more important. In these households, preschoolers received less care from the male and female heads, who spent more time in both the cash crop and in the food crop. In these same households, the nonwork (leisure) time of men increased as a result of VFC participation, but for women, leisure time was unaffected. Thus in the short run, there is perhaps scope for protecting childcare time by reducing time to leisure. In the medium run, benefits may well accrue to unborn preschoolers if VFC participation empowers women.